Efektivitas In Vitro Fertilization (IVF) pada Wanita Usia ≥35 Tahun: Tinjauan Literatur tentang Keberhasilan Kehamilan dan Faktor Prognostik - Haswindah, Haswindah; Syam, Azniah (IAI Nasional Laa Roiba Bogor, 2025)
Infertility in women aged ≥35 year’s poses significant challenges in clinical practice, due to diminished oocyte quality, ovarian reserve, and altered molecular expression of the endometrium. This study aimed to systematically review the effectiveness of In Vitro Fertilization (IVF) in older women and identify key prognostic factors influencing pregnancy outcomes. This is a literature review using a PICO-based search strategy across PubMed, ScienceDirect, Scopus, and Google Scholar databases. Inclusion criteria included human studies published between 2015–2025, in English, peer-reviewed, and full-text accessible. Twenty eligible studies were analyzed to evaluate the relationship between age, ovarian reserve, embryo quality, endometrial gene expression, and IVF success. The results indicate that the success of IVF in women aged ≥35 years is influenced by various factors, such as decreased Anti-Müllerian Hormone (AMH), elevated FSH levels, reduced embryo quality, endometrial thickness and stiffness, as well as disrupted genetic expression of the endometrium. In addition, psychosocial factors, obstetric history, metabolic conditions such as diabetes, and infections (e.g., COVID-19) also serve as important determinants. Technological interventions such as Preimplantation Genetic Testing (PGT), the use of donor oocytes, elective single embryo transfer (eSET), endometrial elastography, and the application of machine learning have been shown to enhance personalization and the success rate of IVF treatment. The conclusion of this review highlights the importance of a multidisciplinary approach based on biomarkers and individualized technologies to improve IVF effectiveness in women aged ≥35 years. These findings are expected to serve as a reference in clinical practice and in the development of evidence-based reproductive health policies.